Cloud Cost Management and Optimization (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
As organizations increasingly migrate to cloud environments, the need to manage costs becomes paramount effectively and efficiently. This paper explores the basic principles and techniques of Cloud Cost. Management and Optimization, focusing on Amazon Web Services (AWS) as a key case study The study delves into the understanding of cloud pricing models, construction emphasize matching pricing plans to specific projects for optimal costs Tools such as Explorer facilitate, search and its role in identifying usage and inefficiencies, explore cost controls with budget constraints and governance systems include implementation to reduce unexpected cost overruns and enhance financial predictability with automation and DevOps They are discussed as important factors in streamlining processes, resources efficiency, and improving overall costs. Through a comprehensive analysis of these principles, the study aims to provide organizations with insights they can use to manage the complexity of cloud cost structures, driving sustainable economic growth and maximize the benefits of cloud computing.